Analysis of Education Budget Allocation, Per Capita Income and Number of Schools on School Participation Rates in Dompu District - Nurul Faizah; Hadi Mahmudi; Endang Astuti (LPPM Sunan Doe, 2023)
This study aims to determine and analyze the effect of the education budget, per capita income and number of schools on school enrollment rates in Dompu Regency in 2012-2021 partially and simultaneously. This study uses a quantitative descriptive method, the data used is secondary data in the form of school enrollment rates (APS), education budget, per capita income and the number of schools obtained from the Central Bureau of Statistics and the Regional Financial and Asset Management Agency. The data obtained was then carried out by using multiple linear regression tests using eviews version 12 software. The results of this study indicate that partially the Education Budget and Number of Schools variables have a significant influence on School Participation Rates in Dompu Regency during the 2012-2021 period, while Per Capita Income did not have a significant effect on the School Participation Rate in Dompu Regency during the 2012-2021 period. Simultaneously the variables of the Education Budget, Per Capita Income and Number of Schools have a significant effect on the School Participation Rate in Dompu Regency during the 2012-2021 period. The results of the classical assumption test stated that there was no detectable multicollinearity, heteroscedasticity and also autocorrelation in the model.